Synthesis of a hybrid underlying surface classifier based on fuzzy logic using current consumption of mobile robot motion; Информационно-управляющие системы; № 1 - Belyaev A. S. Aleksandr Sergeevich (2024, 2024)
Заглавие с экрана.